Microfluidic Impedance‐Deformability Cytometry for Label‐Free Single Neutrophil Mechanophenotyping. Issue 18 (7th March 2022) - Petchakup, Chayakorn; Yang, Haoning; Gong, Lingyan; He, Linwei; Tay, Hui Min; Dalan, Rinkoo; Chung, Aram J.; Li, King Ho Holden; Hou, Han Wei
Abstract: The intrinsic biophysical states of neutrophils are associated with immune dysfunctions in diseases. While advanced image‐based biophysical flow cytometers can probe cell deformability at high throughput, it is nontrivial to couple different sensing modalities (e.g., electrical) to measure other critical cell attributes including cell viability and membrane integrity. Herein, an "optics‐free" impedance‐deformability cytometer for multiparametric single cell mechanophenotyping is reported. The microfluidic platform integrates hydrodynamic cell pinching, and multifrequency impedance quantification of cell size, deformability, and membrane impedance (indicative of cell viability and activation). A newly‐defined "electrical deformability index" is validated by numerical simulations, and shows strong correlations with the optical cell deformability index of HL‐60 experimentally. Human neutrophils treated with various biochemical stimul are further profiled, and distinct differences in multimodal impedance signatures and UMAP analysis are observed. Overall, the integrated cytometer enables label‐free cell profiling at throughput of >1000 cells min −1 without any antibodies labeling to facilitate clinical diagnostics. Abstract : A label‐free and "optics‐free" integrated microfluidic impedance‐deformability cytometer for multiparametric single cell mechanophenotyping is reported. The developed platform utilizes elasto‐inertial focusing to align and deliver the cells to a cross junction for hydrodynamic pinching and biophysical characterization of cell size, deformability, and membrane properties using differential impedance sensing of cells in the native and deformed state.